Feasibility study of SiGHT: a novel ultra low background photosensor for low temperature operation. (27th February 2017) - Wang, Y.; Fan, A.; Fiorillo, G.; Galbiati, C.; Guan, M.Y.; Korga, G.; Pantic, E.; Razeto, A.; Renshaw, A.; Rossi, B.; Suvorov, Y.; Wang, H.; et al.
Abstract: Rare event search experiments, such as those searching for dark matter and observations of neutrinoless double beta decay, require ultra low levels of radioactive background for unmistakable identification. In order to reduce the radioactive background of detectors used in these types of event searches, low background photosensors are required, as the physical size of these detectors become increasing larger, and hence the number of such photosensors used also increases rapidly. Considering that most dark matter and neutrinoless double beta decay experiments are turning towards using noble liquids as the target choice, liquid xenon and liquid argon for instance, photosensors that can work well at cryogenic temperatures are required, 165 K and 87 K for liquid xenon and liquid argon, respectively. The Silicon Geiger Hybrid Tube (SiGHT) is a novel photosensor designed specifically for use in ultra low background experiments operating at cryogenic temperatures. It is based on the proven photocathode plus silicon photomultiplier (SiPM) hybrid technology and consists of very few other, but also ultra radio-pure, materials like fused silica and silicon for the SiPM. The introduction of the SiGHT concept, as well as a feasibility study for its production, is reported in this paper.